An Epidemiological Survey of Venous Disease Among General Practitioner Attendees in Different Geographical Regions on the Globe: The Final Results of the Vein Consult Program. (October 2018) - Vuylsteke, Marc E.; Colman, Roos; Thomis, Sarah; Guillaume, Geneviève; Van Quickenborne, Damien; Staelens, Ivan
This study measured the prevalence of chronic venous disease (CVD, C1-C6), chronic venous insufficiency (C3-C6) in 23 countries. The possible influence of risk factors was assessed. Patient recruitment was carried out by general practitioners. Patient characteristics, prevalence of risk factors, and C-classification were recorded. We assessed differences in prevalence and risk factors between Asia (A), Eastern Europe (EE), Latin America (LA), and Western Europe (WE). A total of 99 359 patients were included. The prevalence of CVD (51.9% A, 70.18% EE, 68.11% LA, and 61.65% WE) was significantly ( P < .001) lower in A. Risk factors such as age, obesity, smoking, having regular exercise, use of birth control pills, prolonged standing and sitting, and having a positive family history differ significantly between regions. After model-based probabilities corrected for risk factors, significant differences in the probability of having CVD were only found in the older age-group (>65 years). The lowest prevalence was noted in A. Chronic venous disease is very common and the prevalence varies between different geographical areas. After correcting for risk factors, these differences diminished.